Teaching practices for English as foreign language at the tertiary level: A comprehensibility perspective - Alzubi, Ali Abbas Falah; Nazim, Mohd; Al-Mwzaiji, Khaled Nasser Ali (Frontiers in Education, 2023)
Comprehension is one of the most crucial factors contributing to acquiring a new language; therefore, teachers must facilitate language comprehensibility using the best teaching practices to help learners understand the target language. This study aimed to identify tertiary EFL teachers’ practices for teaching language comprehensibility to assist in highlighting the comprehensibility practices tertiary EFL teachers employ to ensure that students understand, interact with, and use the English language. To identify the extent that the teachers employ language comprehensibility practices in an EFL context, the descriptive-correlational approach was employed. A closed-item questionnaire was administered to a sample of 65 teachers in Najran University, Saudi Arabia in the academic year 2021-2022. The Statistical Package for Social Sciences (SPSS v. 23) was used to analyze the data. The results showed that tertiary EFL teachers taught language comprehensibility very skillfully. Also, no significant difference in teaching language comprehensibility was found concerning the gender variable. There were, however, differences in the means of the sample’s responses towards methods of teaching language comprehensibility according to years of experience, particularly for those with the most years of experience. Considering the results, the study suggested paying more attention to integrating language comprehensibility practices in EFL contexts.